Social and Environmental Factors Influencing COVID-19 Transmission and Mortalities in Developing and Developed Nations (Epidemiology, Biostatistics, and Public Health, 2024)
Background: The study sought to establish environmental and social factors that influenced the transmission and mortalities of COVID-19 in developing and developed nations. The factors that were assessed included temperature, average age of the population, urbanization, population density, and percentage of old-aged people in the population. The dependent variables were COVID-19 transmission and COVID-19-related deaths. Methods: The study employed a pragmatism research philosophy. It also relied on a deductive research approach and a descriptive research design. It adopted a mixed-method approach as it used both qualitative and quantitative data. It was a cross-sectional study, given its data measurement at a particular point in time. Data was analyzed and presented using descriptive techniques. Results: Statistical analyses were conducted to quantify the relationships between various factors and COVID-19 outcomes. A Kendall’s Tau test revealed a robust negative correlation between COVID-19 cases and temperature (Tb = -0.560, p
Keywords: Medical Education; competition; Young medical doctor; Medical specialities; career choice